Apoptosis inhibition restrains primary malignant traits in different Drosophila cancer models - Sollazzo, Manuela; Paglia, Simona; Di Giacomo, Simone; Grifoni, Daniela (Frontiers in Cell and Developmental Biology, 2023)
Tumor cells exploit multiple mechanisms to evade apoptosis, hence the strategies aimed at reactivating cell death in cancer. However, recent studies are revealing that dying cells play remarkable pro-oncogenic roles. Among the mechanisms promoting cell death, cell competition, elicited by disparities in MYC activity in confronting cells, plays the primary role of assuring tissue robustness during development from Drosophila to mammals: cells with high MYC levels (winners) overproliferate while killing suboptimal neighbors (losers), whose death is essential to process completion. This mechanism is coopted by tumor cells in cancer initiation, where host cells succumb to high-MYC-expressing precancerous neighbors. Also in this case, inhibition of cell death restrains aberrant cell competition and rescues tissue structure. Inhibition of apoptosis may thus emerge as a good strategy to counteract cancer progression in competitive contexts; of note, we recently found a positive correlation between cell death amount at the tumor/stroma interface and MYC levels in human cancers. Here we used Drosophila to investigate the functional role of competition-dependent apoptosis in advanced cancers, observing dramatic changes in mass dimensions and composition following a boost in cell competition, rescued by apoptosis inhibition. This suggests the role of competition-dependent apoptosis be not confined to the early stages of tumorigenesis. We also show that apoptosis inhibition, beside restricting cancer mass, is sufficient to rescue tissue architecture and counteract cell migration in various cancer contexts, suggesting that a strong activation of the apoptotic pathways intensifies cancer burden by affecting distinct phenotypic traits at different stages of the disease.